Classification as “Natural Person” brings tributary advantages to small farme - Santos, Fernanda; Santos, Fernanda Ferreira dos; Brochine, Luciano; Santos, Paula Ferreira dos; Gameiro, Augusto Hauber (Pubvet, 2019)
Agribusiness accounts for almost 25% of Brazil's GDP. However, rural producers, especially small ones, find it difficult to maintain a profitable activity. One of the problems is that the country has a high tax burden. The producer has difficulties in doing a tax planning, mainly for lack of knowledge. This article has as main objective the analysis of the advantages and disadvantages of the rural producer to be framed as netural person or legal entity. In order to do so, it has a review on the concepts of natural person and legal entities for farmers, case studies reported in the literature, comparing tax burdens on corporate activity (by the National Simples, Presumed Income and Real Income) and natural person. In general, the rural producer with rural CNPJ is still classified as a natural person and thus has facilities to generate invoices, has a lower incidence of taxes and advantages in the consumption of water, electricity and the purchase of vehicles. However, depending on revenue at the end of 12 months, other frameworks may be more advantageous and need to be calculated on a case-by-case basis.
Keywords: agribusiness; rural CNPJ; rural producer; Taxation